The Influence of Information Technologies on the Formation of Youth’s Spiritual World View - qizi, Abdulhakimova Fotima Turdiqul (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the role of information and information technologies in the formation of the spiritual outlook of young people is discussed. detailed information about the ways to avoid conflicting foreign ideas, as well as the positive aspects of information technology in the life of young people.